Impact of HR Practices on Job Opportunities and Career Advancement in the Hospitality Industry - Dr. Varinder Singh Rana (Journal of Social Responsibility, Tourism and Hospitality, 2023)
This research aims to explore the current trends and best practices in human resource management, particularly in relation to job advertisements, within the hospitality industry. By examining relevant literature and analyzing case studies, this study seeks to provide valuable insights into effective recruitment strategies, job advertisement optimization, and the impact of technological advancements on HR practices. The findings of this research will contribute to the knowledge base of HR professionals, enabling them to enhance their recruitment efforts and attract and retain talented individuals in the competitive landscape of the hospitality industry.